Bioecology Fungi - Pathogens Flower Crops and The System to Combat Them (Eurasian Research Bulletin, 2022)
For the first time, degree of damage of the disease Botrytis cinerea Pers. founded in decorative colors in the Tashkent region. Chemical preparations are most effective methods of struggle in the fight against diseases ornamental crops.